Mobile X-Space Design, Teaching Strategies and Undergraduate Students Collaborative Learning Behaviour: A Case Study in Taylors University, Malaysia - Lim, Chee Leong; Hassan, Nurhanim; Md Isa, Filzah; Ab Jalil, Habibah (Universiti Utara Malaysia Press, 2018)
Purpose - The availability of new innovative learning spaces together with the introduction of new teaching and learning strategies have shifted the nature of the classroom from a place of instruction towards a place that produces authentic learning. Students in the 21st century are inclined to learn with peers, through the use technology to produce the information as the result of their collaboration. This research examines the effect of learning space design and teaching strategies on undergraduate students collaborative learning behaviour in the Mobile X-Space classroom.